Práticas de leitura literária na educação básica no município de Campina Grande-PB - Sousa, Amasile Coelho Lisboa da Costa (2023)
For many students, mainly from public schools, the school is the only place where they have the opportunity to experience literary texts, allowing them to better understand themselves andthe world in which they live. From this context, the research will seek to investigate literary reading practicesin the final years of elementary school in public schools in the city of CampinaGrande-PB. To pursue this objective, we followed the following methodological path: i) we interviewed 13 teachers in order to understand the literary reading practices that are being produced in schools; ii) we analyzed official documents from the municipality of Campina Grande, place where the schools are located, in addition to other documents at national level and, finally, iii) We produced a Field Diary that allowed us to discover particularities from thevisit to the schools investigated. We are, therefore, now undertaking field research, of a documentary nature, that will enable us to diagnose literary reading practices, giving them due visibility. For data analysis, we appropriated external reflections for the formation of the literary reader in which we highlight the works of Zilberman and Lajolo (2019), Colomer (2007), Bordini and Aguiar (1988), Pinheiro (2018), Yunes ( 2002), Castrillón (2011), Lerner (2002), Bajard (2001), Tardif (2007), among others. As a result, we took a reflective look at the processof training literary readers in public schools in the city of Campina Grande-PB. Despite so many difficulties perceived in daily school life – conflicts, violence, discouragement on the part of some teachers, deficient physical structure and lack of external public policies for the reading of literary texts –, we found in many of the schools surveyed creative practices which, if presentimprovements and continuity, will make a great contribution to the process of training the literary reader.